Microbubble absorption and gas-liquid separation device and application thereof in carbon dioxide absorption

By using the membrane separation technology used by Janus separation membrane and hydrophobic separation membrane in the CO2 chemical absorption tower, the problems of small gas-liquid contact area and poor operating stability in the traditional absorption tower are solved, and efficient CO2 absorption and gas-liquid separation are achieved. , reduces costs and improves stability.

CN119488783AActive Publication Date: 2025-02-21DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311064095.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-02-21
Estimated Expiration
2043-08-21

AI Technical Summary

Technical Problem

The existing CO2 chemical absorption tower has a small gas-liquid contact area and insufficient mass transfer driving force, resulting in high equipment investment and operation costs and poor operating stability.

Method used

The Janus separation membrane and hydrophobic separation membrane are used to replace traditional absorption towers and gas-liquid separation devices. The gas-liquid contact area and mass transfer efficiency are improved through membrane separation technology, and equipment investment and operation energy consumption are reduced.

Benefits of technology

The gas-liquid contact area and mass transfer efficiency are greatly improved, the investment and operating costs of CO2 absorption and gas-liquid separation devices are reduced, and the operation stability is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488783A_ABST
    Figure CN119488783A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon dioxide microbubble absorption device. Comprising a microbubble dispersion device, an absorption device and a gas-liquid separation device, the microbubble dispersing device is filled with a Janus hollow fiber membrane; the water contact angle of the hydrophilic layer of the Janus hollow fiber membrane is less than 70 degrees, and the water contact angle of the hydrophobic layer is greater than 100 degrees; the gas-liquid separation device is filled with a hydrophobic separation membrane; the hydrophobic separation membrane is selected from at least one of a polytetrafluoroethylene hollow fiber membrane, a polypropylene hollow fiber membrane and a polyvinylidene fluoride hollow fiber membrane. And the purpose of continuously preparing the micron-sized bubbles at low cost is achieved through the Janus separation membrane. The gas-liquid mass transfer can be greatly enhanced by utilizing the micron-sized bubbles, the CO2 absorption efficiency is improved, and the CO2 concentration in the rich absorption liquid is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a microbubble absorption and gas-liquid separation device and its application in carbon dioxide absorption, belonging to the technical field of chemical separation. Background Art

[0002] Carbon dioxide emission reduction is a global issue that is closely related to economic and social development and energy utilization. Therefore, it requires close cooperation among multiple countries to jointly resolve it.

[0003] In my country, coal-fired power plants are fixed and concentrated sources of CO2 emissions, accounting for more than 70% of power generation, and CO2 emissions account for more than 95% of the total CO2 emissions from power generation. The flue gas of coal-fired power plants has the characteristics of large flow, low CO2 partial pressure in flue gas, and stable flow. On the one hand, this facilitates the development of the CO2 capture process. On the other hand, due to the CO2 partial pressure, more energy is required in the capture process. The absorbent-based CO2 chemical absorption technology was first proposed in 1930, mainly used for the removal of CO2 from natural gas. Later, some scholars proposed to use this technology to remove CO2 from flue gas emitted by coal-fired power plants. The chemical absorption process device mainly includes pretreatment tower, absorption device (tower), regeneration device (tower), lean-rich liquid heat exchanger, reboiler and other main equipment. Chemical absorption is the most mature carbon capture technology in recent stages. At present, the main factor limiting the large-scale commercial application of chemical absorption is the high investment cost of the technology and the high cost of chemical absorption device during operation.

[0004] One of the problems that restricts the high cost of CO2 chemical absorption towers is that the mixed gas containing CO2 flows in the absorption tower in millimeter-centimeter-level airflow or bubbles, the contact area between gas and liquid is small, and the gas-liquid mass transfer is limited, resulting in a large volume of absorption towers, complex structures, and high fixed cost investment. In addition, problems such as flooding, entrainment, and channeling during the operation of packed towers or absorption towers seriously restrict the stable operation of the chemical absorption process.

[0005] The essence of chemical absorption is a gas-liquid reaction process, and mass transfer and reaction rate are the key factors that restrict the chemical absorption rate. The mass transfer rate is determined by the change in gas composition before and after treatment and the gas-liquid contact area, and the reaction rate is mainly affected by the properties of the absorbent. The main problem with the chemical absorption method is that the equipment investment and operating costs are too high, which has become a bottleneck restricting its application in the CO2 capture process. Under the condition that the flue gas capture rate of the power plant is 90%, the equipment investment for chemical absorption is 2000-4000 yuan / kW, accounting for about 70% of the power plant investment, and the operating cost is 250-300 yuan / ton of CO2. In terms of equipment investment, the existing absorption devices are mostly bubble towers, absorption towers, etc. Such devices have a small specific surface area and can only produce millimeter-level bubbles or airflows. The gas-liquid contact area is insufficient and the mass transfer efficiency is low, resulting in a large absorption equipment, high investment, and problems such as channeling and flooding during operation. In terms of operating costs, the organic amine solution needs to be heated from 40°C to 100-120°C to complete CO2 desorption, and the absorption liquid contains a large amount of water with high specific heat, resulting in high desorption energy consumption. The energy consumption of the chemical absorption stage accounts for 60-70% of the entire carbon capture process.

[0006] Compared with millimeter-sized bubbles, micron-sized bubbles have the following advantages in the chemical absorption process:

[0007] (1) Increased gas-liquid contact area

[0008] As the particle size of microbubbles decreases, the gas-liquid contact area increases significantly. If the average particle size of microbubbles is about 50-100 μm, the effective gas-liquid contact area is 50-100 times that of the traditional bubble tower, which greatly enhances the gas-liquid mass transfer rate.

[0009] (2) High CO2 partial pressure

[0010] For microbubbles, due to the small radius of curvature and the liquid tension on their outer surface, the pressure inside the bubble is higher than the pressure of the liquid at the location. The higher pressure P follows the Young-Laplace equation:

[0011] Gas pressure in microbubbles P = 2σ / r(1)

[0012] In formula (1), σ is the surface tension of the liquid phase; r is the radius of the microbubble. The smaller the size of the microbubble particles, the higher the gas pressure inside them, which leads to an increase in the CO2 partial pressure inside the bubble, an increase in the driving force of the gas film mass transfer, and an enhancement of the gas phase mass transfer;

[0013] (3) Improved mass transfer capacity

[0014] According to literature research, compared with large bubbles, the gas film and liquid film of microbubbles are thinner, the mass transfer coefficient is improved, and the mass transfer distance is shortened, which can effectively increase the gas-liquid mass transfer rate.

[0015] (4) Microbubbles have a carrying effect, improving operational stability

[0016] As the bubble size decreases, the probability of bubble aggregation decreases, the buoyancy of the bubbles in the absorption liquid decreases, and the bubbles and the absorption liquid are in a stable foam fluid state. Bubbling, flooding and other phenomena in the absorption tower will not occur, and the operating stability is greatly increased.

[0017] In summary, microbubbles are superior to millimeter-sized bubbles in the absorption tower in terms of gas-liquid mass transfer area and mass transfer coefficient. The applicant intends to prepare CO2-containing flue gas or mixed gas into 50-100μm microbubbles and disperse them in the absorption liquid, and use the characteristics of microbubbles to strengthen the chemical absorption process, which is expected to break the restrictions on the types and concentrations of absorbents in existing absorption devices, broaden the scope of use of absorbent types and concentrations, significantly reduce the volume and investment of chemical absorption devices, reduce the energy consumption and operating costs of the desorption process, and provide new ideas for chemical absorption decarbonization technology.

[0018] Flue gas has a large emission volume and low CO2 content. In order to achieve better chemical absorption efficiency, the microbubble preparation technology should meet the characteristics of large gas production, low production cost and narrow bubble particle size distribution. Microbubble preparation technologies include: pressurized dissolved gas release method, dispersed air method, electrolysis method, air flotation pump gas production method, etc., but these technologies have high energy consumption, wide bubble diameter distribution, limited by gas solubility, low gas production efficiency and other shortcomings, and are not suitable for the chemical absorption process of flue gas. The method of preparing microbubbles by dispersing gas with microporous membrane can meet the above requirements, but the wetting problem of membrane pores limits its long-term use.

[0019] Preparation methods and performance comparison of microbubbles

[0020]

[0021] Therefore, the Janus separation membrane can prepare microbubbles continuously at low cost, and is particularly suitable for the decarbonization process of CO2 mixed gases with large gas volumes such as flue gas. However, the characteristics of microbubbles lead to serious foaming during the chemical absorption process. The appearance of foam can lead to serious gas-liquid entrainment problems. In actual operation, demisters need to be added to both the absorption tower and the packed tower to facilitate the removal of foam, but the defoaming effect is not good. During use, there is still a large amount of foam entrainment, resulting in unstable operation and a large amount of absorbent loss. Therefore, how to improve the defoaming effect of the gas-liquid separation device is of great significance to improving the stable operation of microbubble technology in the CO2 chemical absorption process. Summary of the invention

[0022] In response to this problem, the present application uses a hollow fiber hydrophobic membrane with a high specific surface area and high penetration pressure for gas-liquid separation. The high specific surface area of ​​the hydrophobic membrane is used to increase the probability of contact between the foam and the membrane material, thereby enhancing the foam removal effect. The membrane pores of the hydrophobic membrane can also be used to block the absorption liquid, while the removed gas is discharged from the membrane pores to achieve gas-liquid separation. Compared with the traditional gas-liquid separation device, it has the advantages of small size, high defoaming efficiency, suppression of gas-liquid entrainment, and reduced loss of absorbent.

[0023] In the process of capturing CO2 by chemical absorption, the high equipment investment and operating costs are caused by the small gas-liquid contact area and insufficient mass transfer driving force in the traditional absorption tower.

[0024] To solve the above problems, the present application adopts a combination of Janus separation membrane and hydrophobic separation membrane to replace the absorption tower and gas-liquid separation device in the traditional absorption process, greatly increase the gas-liquid contact area, enhance mass transfer, and reduce equipment investment and operating energy consumption in the chemical absorption process.

[0025] The CO2 absorption and gas-liquid separation method based on the combination of Janus separation membrane and hydrophobic separation membrane is characterized in that membrane separation technology is used to replace traditional absorption towers and gas-liquid separation devices.

[0026] According to one aspect of the present application, a carbon dioxide microbubble absorption device is provided, the carbon dioxide microbubble absorption device comprising a microbubble dispersion device, an absorption device, and a gas-liquid separation device;

[0027] The microbubble dispersion device is filled with a Janus hollow fiber membrane;

[0028] The water contact angle of the hydrophilic layer of the Janus hollow fiber membrane is less than 70°, and the water contact angle of the hydrophobic layer is greater than 100°;

[0029] Optionally, the water contact angle of the hydrophilic layer is less than 65°, and the water contact angle of the hydrophobic layer is greater than 110°.

[0030] The Janus hollow fiber membrane has an inner diameter of 0.7-0.8 mm, an outer diameter of 1.2-1.4 mm, and a pore size of 0.2-0.3 μm;

[0031] The length of the membrane fibers of the Janus hollow fiber membrane ranges from 20 to 100 cm;

[0032] The gas-liquid separation device is filled with a hydrophobic separation membrane;

[0033] The hydrophobic separation membrane is selected from at least one of a polytetrafluoroethylene hollow fiber membrane, a polypropylene hollow fiber membrane, and a polyvinylidene fluoride hollow fiber membrane.

[0034] The length of the membrane filaments of the hydrophobic separation membrane ranges from 20 to 100 cm;

[0035] The microbubble dispersion device is provided with an inlet I-1, an inlet I-2, and an outlet I;

[0036] The inlet I-1 is the absorption liquid inlet;

[0037] The inlet I-2 is a mixed gas inlet;

[0038] The absorption device is provided with an inlet II and an outlet II;

[0039] The gas-liquid separation device is provided with an inlet III, an outlet III-1, and an outlet III-2.

[0040] The outlet I is connected to the inlet II pipeline;

[0041] The outlet II is connected to the inlet III through a pipeline.

[0042] The Janus hollow fiber membrane is obtained by the following steps:

[0043] The inner layer membrane-making liquid and the outer layer membrane-making liquid are introduced into the spinning core liquid by using a double-channel nozzle, and co-extruded to obtain a double-layer hollow fiber membrane, and the modified monomer is grafted to obtain the Janus hollow fiber membrane;

[0044] The inner layer film-making solution contains a film-forming polymer A, an inner layer additive, an organic solvent A and an amphiphilic polymer A;

[0045] The outer layer film-making solution contains a film-forming polymer B, an outer layer additive, an organic solvent B and an amphiphilic polymer B;

[0046] The amphiphilic polymer A and the amphiphilic polymer B are independently selected from amphiphilic polymer I and amphiphilic polymer II;

[0047] The amphiphilic polymer contains a hydrophilic structure and a hydrophobic structure. One of the amphiphilic polymers contains a hydroxyl group and a hydrophobic group, and is named as amphiphilic polymer I. The other amphiphilic polymer is named as amphiphilic polymer II. The amphiphilic polymer is synthesized by free radical polymerization, and a hydrophilic monomer and a hydrophobic monomer are selected, and the monomer contains an olefin structure.

[0048] The amphiphilic polymer I is obtained by polymerizing a hydrophilic monomer I and a hydrophobic monomer I;

[0049] The amphiphilic polymer II is obtained by polymerizing a hydrophilic monomer II and a hydrophobic monomer II;

[0050] The hydrophilic monomer I is selected from an olefin monomer containing a hydroxyl group, specifically selected from at least one of allyl alcohol and butenol;

[0051] The hydrophilic monomer II is selected from at least one of polyethylene glycol acrylate and vinyl pyrrolidone;

[0052] The hydrophobic monomer I and the hydrophobic monomer II are independently selected from at least one of styrene, methyl acrylate, acrylonitrile and hexafluorobutyl acrylate;

[0053] The amphiphilic polymer A in the inner layer film-forming solution and the amphiphilic polymer B in the outer layer film-forming solution are different from each other;

[0054] The modified monomer is selected from at least one of hexafluorohexyltriethoxysilane and tridecafluorooctyltriethoxysilane.

[0055] The film-forming polymer A and the film-forming polymer B are independently selected from at least one of polysulfone, polyethersulfone, polyvinylidene fluoride, polymethyl methacrylate, polyvinyl chloride and polyacrylonitrile;

[0056] The inner layer additive is selected from at least one of polyethylene glycol, anhydrous lithium chloride and polyvinyl pyrrolidone;

[0057] The outer layer additive is selected from at least one of polyethylene glycol, anhydrous lithium chloride and polyvinyl pyrrolidone;

[0058] The organic solvent A and the organic solvent B are independently selected from at least one of dimethylacetamide, dimethylformamide, N-methylpyrrolidone and tetrahydrofuran;

[0059] The mass concentration of the film-forming polymer A in the inner layer film-forming solution is 10-25wt%, the mass concentration of the inner layer additive is 5-20wt%, and the mass concentration of the amphiphilic polymer A is 1-20wt%;

[0060] Optionally, the mass concentration of the film-forming polymer A in the inner film-forming solution is any value selected from 10wt%, 15wt%, 20wt%, 25wt%, or a range between any two of them; the mass concentration of the inner layer additive is any value selected from 5wt%, 10wt%, 15wt%, 20wt%, or a range between any two of them; and the mass concentration of the amphiphilic polymer A is any value selected from 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, or a range between any two of them;

[0061] The mass concentration of the film-forming polymer B in the outer layer film-forming solution is 10-25 wt %, the mass concentration of the outer layer additive is 5-20 wt %, and the mass concentration of the amphiphilic polymer B is 1-20 wt %.

[0062] Optionally, the mass concentration of the film-forming polymer B in the outer layer film-forming solution is any value among 10wt%, 15wt%, 20wt%, 25wt%, or a range between any two of them; the mass concentration of the outer layer additive is any value among 5wt%, 10wt%, 15wt%, 20wt%, or a range between any two of them; and the mass concentration of the amphiphilic polymer B is any value among 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, or a range between any two of them;

[0063] The polymerization temperature is 50 to 80°C;

[0064] Optionally, the polymerization temperature is any value of 50°C, 60°C, 70°C, 80°C, or any range between the two;

[0065] The polymerization time is 40 to 600 minutes;

[0066] Optionally, the polymerization time is any value of 40 min, 600 min, or any range between the two.

[0067] The polymerization is carried out in the presence of a catalyst;

[0068] The catalyst is selected from at least one of azobisisobutyronitrile and benzoyl peroxide.

[0069] The grafting modification monomer comprises the following steps:

[0070] immersing the double-layer hollow fiber membrane in a solvent solution containing a modified monomer;

[0071] The solvent is selected from at least one of n-hexane, cyclohexane, n-heptane, toluene, ethylbenzene and ethyl acetate;

[0072] In the solvent solution containing the modified monomer, the mass ratio of the modified monomer to the solvent is 0.01 to 0.15:1.

[0073] Optionally, in the solvent solution containing the modified monomer, the mass ratio of the modified monomer to the solvent is any value among 0.01:1, 0.05:1, 0.15:1, or a range value between any two of them.

[0074] The inner layer film-making liquid is stirred I;

[0075] The stirring temperature is 10-120°C;

[0076] Optionally, the stirring temperature I is any value of 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, or any range between two values.

[0077] The stirring time I is 1 to 20 hours.

[0078] Optionally, the stirring time I is any value among 1h, 5h, 10h, 15h, 20h, or a range value between any two of them.

[0079] The outer film-making liquid is stirred II;

[0080] The stirring temperature of II is 10 to 120° C.

[0081] Optionally, the stirring temperature II is any value of 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, or any range between two of them.

[0082] The stirring time II is 1 to 20 hours.

[0083] Optionally, the stirring time II is any value among 1h, 5h, 10h, 15h, 20h, or a range value between any two of them.

[0084] The spinning core liquid is selected from water or an aqueous solution containing ethanol, methanol, or an organic solvent;

[0085] The mass concentration of the aqueous solution containing ethanol, methanol or an organic solvent is 10-80 wt %.

[0086] The total extrusion rate of the inner film-forming liquid and the outer film-forming liquid is 3 to 20 mL / min;

[0087] Optionally, the total extrusion volume of the inner film-forming liquid and the outer film-forming liquid is any value among 3 mL / min, 5 mL / min, 10 mL / min, 15 mL / min, 20 mL / min, or a range value between any two of them.

[0088] The ratio of the extrusion amount of the inner layer film-forming liquid to the extrusion amount of the outer layer film-forming liquid is 0.1 to 10:1.

[0089] Optionally, the ratio of the extrusion amount of the inner film-forming liquid to the outer film-forming liquid is any value among 0.1:1, 0.5:1, 1:1, 5:1, 10:1, or a range value between any two of them.

[0090] The double-layer hollow fiber membrane is gel-formed;

[0091] The solution used for gel forming is selected from water or an aqueous solution containing ethanol, methanol, or an organic solvent.

[0092] The mass concentration of the aqueous solution containing ethanol, methanol or an organic solvent is 10-80 wt %.

[0093] The Janus hollow fiber membrane is washed, solvent exchanged, and dried;

[0094] The washing is water washing;

[0095] The solvent exchange is performed using ethanol and n-hexane as solvents;

[0096] The drying method is natural air drying or ethanol-n-hexane replacement air drying.

[0097] By changing the composition, flow rate, core liquid and gel bath composition of the inner and outer membrane-making liquids, Janus hollow fiber membranes with different hydrophilic / hydrophobic layer thicknesses, hydrophilicity and hydrophobicity, and pore structures can be prepared.

[0098] The packing density of the Janus hollow fiber membrane packed in the microbubble dispersion device is 5 to 65%.

[0099] The packing density of the hydrophobic separation membrane packed in the gas-liquid separation device is 5 to 65%.

[0100] The number of the microbubble dispersion device and the gas-liquid separation device is independently selected from a positive integer between 1 and 10;

[0101] Multiple microbubble dispersion devices are connected in series / parallel with each other;

[0102] Multiple gas-liquid separation devices are connected in series / parallel with each other.

[0103] According to another aspect of the present application, a carbon dioxide absorption and gas-liquid separation method is provided, using the above-mentioned carbon dioxide microbubble absorption device.

[0104] (1) Using Janus separation membrane instead of absorption tower, the mixed gas containing CO2 is converted into microbubbles through Janus separation membrane and dispersed in absorbent solution to form CO2-rich absorption liquid;

[0105] (2) A polytetrafluoroethylene separation membrane is used to replace the gas-liquid separation device, and a membrane contactor is constructed through the polytetrafluoroethylene separation membrane to defoam the CO2-rich absorption liquid foam and complete the gas-liquid separation.

[0106] The CO2 absorption and gas-liquid separation method based on the combination of Janus separation membrane and hydrophobic separation membrane adopts a device including an absorption liquid storage tank, a centrifugal pump, a Janus membrane assembly, a CO2 mixed gas, an absorption tube, a gas-liquid separator, and a gas flow meter, which are connected in sequence, and the liquid outlet of the gas-liquid separation tank is connected to the feed port of the absorption liquid storage tank, and the outlet of the absorption liquid storage tank is connected to the liquid inlet of the Janus membrane assembly. The CO2-containing mixed gas flows in from the hydrophobic layer of the Janus membrane, flows out from the hydrophilic layer, and forms microbubbles after contacting with the absorbent. The microbubbles react with the absorbent inside the Janus membrane assembly and the absorption tube to obtain a CO2-rich absorption liquid;

[0107] In the carbon dioxide microbubble absorption device, the gas pressure is 0.02-10 MPa, the liquid pressure is 0.01-10 MPa, and the gas-pressure differential is 0.001-0.3 MPa.

[0108] The membrane contactor constructed with polytetrafluoroethylene hollow fiber is used for gas-liquid separation of CO2-rich absorption liquid. The gas-liquid separation device includes a rich liquid delivery pump, a polytetrafluoroethylene hollow fiber membrane assembly, and a valve. Each component is connected in sequence.

[0109] The CO2-rich absorption liquid is pumped into the shell side of the polytetrafluoroethylene hollow fiber membrane module through a rich liquid delivery pump to increase the pressure. After the CO2-rich absorption liquid contacts the polytetrafluoroethylene hollow fiber membrane, the foam is squeezed and burst, and the gas is discharged from the membrane pores. The absorption liquid with gas removed is retained by the hydrophobic membrane pores and flows out from the shell side of the polytetrafluoroethylene hollow fiber membrane module to achieve gas-liquid separation.

[0110] In the gas-liquid separation device, the temperature is 10-60° C. and the pressure is 0.01-0.05 MPa.

[0111] Optionally, in the gas-liquid separation device, the temperature is 40-60°C and the pressure is 0.02-0.04Mpa.

[0112] The beneficial effects of this application include:

[0113] (1) The carbon dioxide microbubble absorption device and CO2 absorption / gas-liquid separation method provided by the present application achieve the purpose of low-cost and continuous preparation of micron-sized bubbles through Janus separation membrane. The use of micron-sized bubbles can greatly enhance gas-liquid mass transfer, improve CO2 absorption efficiency, and increase CO2 concentration in rich absorption liquid;

[0114] (2) The carbon dioxide microbubble absorption device and CO2 absorption / gas-liquid separation method provided in the present application achieve foam elimination and enhance gas-liquid separation through the high specific surface area and hydrophobicity of the hydrophobic hollow fiber membrane;

[0115] (3) The carbon dioxide microbubble absorption device and CO2 absorption / gas-liquid separation method provided in the present application can significantly reduce the investment and operating costs of the CO2 absorption and gas-liquid separation devices, and have the advantages of small size, light weight and wide application range. BRIEF DESCRIPTION OF THE DRAWINGS

[0116] Figure 1 Schematic diagram of the microbubble absorption and desorption device described in Example 1 of the present application; wherein: (1) an absorption liquid storage tank, (2) a centrifugal pump, (3) a Janus membrane assembly (microbubble dispersion device), (4) a CO2 mixed gas, (5) an absorption tube, and (6) a gas-liquid separation device.

[0117] Figure 2 Schematic diagram of the gas-liquid separation device in the microbubble absorption and desorption device described in Example 1 of the present application; wherein: (7) CO2-rich absorption liquid inlet, (8) rich liquid booster pump, (9) hydrophobic hollow fiber membrane contactor, (10) valve, (11) desorption tower, and (12) CO2 gas outlet. DETAILED DESCRIPTION

[0118] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0119] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0120] Device example 1

[0121] Figure 1 This is a schematic diagram of microbubble absorption described in Example 1 of the present application;

[0122] (1) The absorption liquid storage tank is connected to (3) the Janus membrane module via (2) a centrifugal pump pipeline;

[0123] (4) The CO2 mixed gas is connected to (3) the Janus membrane module pipeline;

[0124] (3) The Janus membrane module is connected to (5) the absorption pipe;

[0125] (5) The absorption tube is connected to (6) the gas-liquid separator pipeline.

[0126] Figure 2 This is a schematic diagram of the gas-liquid separation device described in Example 1 of the present application;

[0127] (7) The CO2-rich absorption liquid inlet enters (9) the hydrophobic hollow fiber membrane contactor via (8) the rich liquid booster pump, and the carbon dioxide gas is discharged through (12) the CO2 gas outlet. The liquid is controlled by the (10) valve to flow into the (11) desorption tower for desorption.

[0128] Preparation Example 1

[0129] Take 8g of acryl alcohol and 2g of styrene, dissolve them in 415g of dimethylacetamide, add 0.1g of azobisisobutyronitrile, introduce nitrogen, heat and stir at 50°C for 40min to obtain a solution containing amphiphilic polymer I. Add 50g of PVDF and 25g of polyethylene glycol 400 to this solution to obtain an inner layer membrane solution.

[0130] Take 20g of vinyl pyrrolidone and 5g of styrene, dissolve them in 350g of dimethylacetamide, add 0.5g of azobisisobutyronitrile, heat and stir at 60℃ for 80min to obtain a solution containing amphiphilic polymer II. Add 100g of PVDF and 25g of polyethylene glycol 400 to this solution to obtain an outer layer film-making solution.

[0131] The inner film-making liquid and the outer film-making liquid are added to the inner film-making liquid spinning tank and the outer film-making liquid spinning tank respectively, and vacuum degassing is carried out for 24 hours. The outer film-making liquid and the inner film-making liquid are respectively injected into the double-channel nozzle, and ethanol is used as the core liquid and deionized water is used as the outer gel bath to spin a double-layer hollow fiber membrane. The flow rate of the outer film-making liquid is 5ml / min, and the inner film-making liquid is 0.5ml / min to obtain a double-layer hollow fiber membrane. The obtained double-layer hollow fiber membrane is immersed in the grafting modification solution, and the grafting reaction is carried out for 24 hours. The composition of the grafting modification solution is 1g of hexafluorohexyltriethoxysilane and 100g of n-hexane. The grafted double-layer membrane is rinsed in deionized water for 48 hours, and ethanol-n-hexane is replaced and dried successively to obtain a Janus hollow fiber membrane. The Janus membrane has a hydrophobic inner layer and a hydrophilic outer layer structure.

[0132] Example 1

[0133] The apparatus described in Apparatus Example 1 was used. The Janus membrane obtained in Preparation Example 1 was used.

[0134] The outer layer is a hydrophilic layer with a water contact angle of 35°, and the inner layer is a hydrophobic layer with a water contact angle of 135°. The inner diameter of the hollow fiber membrane is 0.7 mm, the outer diameter is 1.2 mm, and the pore size of the Janus membrane is 0.3 μm. 300 hollow fiber membranes are taken to make a hollow fiber membrane assembly, the membrane fiber packing density is 55%, and the effective length is 100 cm.

[0135] Take N2 / CO2 mixed gas (N2 accounts for 85%, CO2 accounts for 15%), absorbent (composed of 5% anhydrous piperazine, 38% N-methyl-diethanolamine, 57% deionized water), pressurize the mixed gas into the Janus membrane module from the air inlet of the Janus membrane module, flow into the membrane of the Janus hollow fiber membrane from the outer surface of the Janus hollow fiber membrane and combine with the absorbent to form microbubbles. The pressure of the mixed gas is 0.15MPa, and the pressure of the absorbent is 0.02MPa. The microbubbles combine with the absorbent inside the membrane module and in the subsequent absorption tube, and gas-liquid separation is achieved through the gas-liquid separator to test the CO2 content in the mixed gas.

[0136] The test results are as follows: the average diameter of the microbubbles in the mixed gas is 30μm, and the processing volume of the mixed gas is 7m 3 / m 2 h. The CO2 absorption rate in the mixed gas after absorption is 99.97%, and the absorption rate of the absorption liquid can reach 75%, which can operate stably for a long time.

[0137] The gas-liquid separator is composed of a polytetrafluoroethylene hollow fiber membrane assembly. The water contact angle of the polytetrafluoroethylene separation membrane is 115°, the packing density of the hollow fiber membrane assembly is 55%, and the length of the membrane assembly is 100 cm. The CO2-rich absorption liquid flows through the hollow fiber membrane assembly, pressurized to 0.03 MPa, and flows into the shell of the hollow fiber membrane contactor. After the absorption liquid contacts the hollow fiber membrane, bubbles are eliminated, and the gas flows out through the membrane pores.

[0138] After the bubbles are removed, the CO2-rich absorption liquid flows out and can enter the desorption tower for desorption.

[0139] The gas content in the CO2-rich absorption liquid is more than 85% before entering the gas-liquid separation device, and the gas content is less than 2% after flowing through the polytetrafluoroethylene hollow fiber membrane module.

[0140] Preparation Example 2

[0141] Take 30g of butenol and 10g of methyl methacrylate, dissolve them in 350g of dimethylacetamide, add 0.1g of azobisisobutyronitrile, introduce nitrogen, heat and stir at 70°C for 200min to obtain a solution containing amphiphilic polymer I. Add 100g of polyethersulfone and 20g of anhydrous lithium chloride to this solution to obtain an outer layer film-forming solution.

[0142] Take 40g of polyethylene glycol acrylate and 10g of methyl acrylate, dissolve them in 360g of dimethylacetamide, add 0.5g of azobisisobutyronitrile, and heat and stir the mixture at 60°C for 400min to obtain a solution containing amphiphilic polymer II. Add 70g of polyethersulfone and 20g of anhydrous lithium chloride to the solution to obtain an inner layer film-forming solution.

[0143] The inner film-making liquid and the outer film-making liquid are added to the inner film-making liquid spinning tank and the outer film-making liquid spinning tank respectively, and vacuum degassing is carried out for 24 hours. The outer film-making liquid and the inner film-making liquid are respectively injected into the double-channel nozzle, and water is used as the core liquid and propanol is used as the outer gel bath to spin a double-layer hollow fiber membrane. The flow rate of the outer film-making liquid is 1.5ml / min, and the inner film-making liquid is 3.5ml / min to obtain a double-layer hollow fiber membrane. The obtained double-layer hollow fiber membrane is immersed in the grafting modification solution, and the grafting reaction is 24 hours. The composition of the grafting modification solution is 5g hexafluorohexyltriethoxysilane and 95g toluene. The grafted double-layer membrane is rinsed in deionized water for 48 hours, and ethanol-n-hexane is replaced and dried successively to obtain a Janus hollow fiber membrane. The Janus membrane has a hydrophobic outer layer and a hydrophilic inner layer structure.

[0144] Example 2

[0145] The apparatus described in Apparatus Example 1 was used. The Janus membrane obtained in Preparation Example 2 was used.

[0146] The outer layer is a hydrophilic layer with a water contact angle of 25°, and the inner layer is a hydrophobic layer with a water contact angle of 125°. The inner diameter of the hollow fiber membrane is 0.8 mm, the outer diameter is 1.2 mm, and the pore size of the Janus membrane is 0.2 μm. 200 hollow fiber membranes are taken to make a hollow fiber membrane assembly, the membrane fiber packing density is 50%, and the effective length is 100 cm.

[0147] Take N2 / CO2 mixed gas (N2 accounts for 88%, CO2 accounts for 12%), absorbent (composed of 5% anhydrous piperazine, 38% N-methyl-diethanolamine, 57% deionized water), pressurize the mixed gas into the Janus membrane module from the air inlet of the Janus membrane module, flow into the membrane of the Janus hollow fiber membrane from the outer surface of the Janus hollow fiber membrane and combine with the absorbent to form microbubbles. The pressure of the mixed gas is 0.1MPa, and the pressure of the absorbent is 0.02MPa. The microbubbles combine with the absorbent inside the membrane module and in the subsequent absorption tube, and the gas-liquid separation is achieved through the gas-liquid separator to test the CO2 content in the mixed gas.

[0148] The test results are as follows: the average diameter of the microbubbles in the mixed gas is 60μm, and the processing volume of the mixed gas is 3m 3 / m 2 h. The CO2 absorption rate in the mixed gas after absorption is 99.95%, and the absorption rate of the absorption liquid can reach 75%, which can operate stably for a long time.

[0149] The gas-liquid separator is composed of a polypropylene hollow fiber membrane assembly. The water contact angle of the polypropylene separation membrane is 110°, the packing density of the hollow fiber membrane assembly is 65%, and the length of the membrane assembly is 100 cm. The CO2-rich absorption liquid flows through the hollow fiber membrane assembly, pressurized to 0.02 MPa and flows into the shell of the hollow fiber membrane contactor. After the absorption liquid contacts the hollow fiber membrane, bubbles are eliminated, and the gas flows out through the membrane holes. After the bubble-free CO2-rich absorption liquid flows out, it can also enter the desorption tower for desorption.

[0150] The gas content in the CO2-rich absorption liquid is more than 78% before entering the gas-liquid separation device, and the gas content is less than 3% after flowing through the polytetrafluoroethylene hollow fiber membrane module.

[0151] Example 3

[0152] The apparatus described in Apparatus Example 1 was used.

[0153] The Janus separation membrane made of polyvinylidene fluoride material has a hydrophilic outer layer with a water contact angle of 55° and a hydrophobic inner layer with a water contact angle of 140°. The inner diameter of the hollow fiber membrane is 0.8mm, the outer diameter is 1.4mm, and the pore size of the Janus membrane is 0.2μm. 200 hollow fiber membranes are taken to make a hollow fiber membrane assembly, with a membrane fiber packing density of 53% and an effective length of 100cm.

[0154] Take N2 / CO2 mixed gas (N2 accounts for 83%, CO2 accounts for 17%), absorbent (composed of 5% anhydrous piperazine, 38% N-methyl-diethanolamine, 57% deionized water), pressurize the mixed gas into the Janus membrane module from the air inlet of the Janus membrane module, flow into the membrane of the Janus hollow fiber membrane from the outer surface of the Janus hollow fiber membrane and combine with the absorbent to form microbubbles. The pressure of the mixed gas is 0.1MPa, and the pressure of the absorbent is 0.02MPa. The microbubbles combine with the absorbent inside the membrane module and in the subsequent absorption tube, and the gas-liquid separation is achieved through the gas-liquid separator to test the CO2 content in the mixed gas.

[0155] The test results are as follows: the average diameter of the microbubbles in the mixed gas is 50μm, and the processing volume of the mixed gas is 4m 3 / m 2 h. The CO2 absorption rate in the mixed gas after absorption is 99.95%, and the absorption rate of the absorption liquid can reach 85%, which can operate stably for a long time.

[0156] The gas-liquid separator is composed of a polyvinylidene fluoride hollow fiber membrane assembly. The water contact angle of the polyvinylidene fluoride separation membrane is 145°, the packing density of the hollow fiber membrane assembly is 55%, and the length of the membrane assembly is 100 cm. The CO2-rich absorption liquid flows through the hollow fiber membrane assembly, pressurized to 0.05 MPa and flows into the shell of the hollow fiber membrane contactor. After the absorption liquid contacts the hollow fiber membrane, bubbles are eliminated, and the gas flows out through the membrane holes. After the bubble-free CO2-rich absorption liquid flows out, it can also enter the desorption tower for desorption.

[0157] The gas content in the CO2-rich absorption liquid is more than 78% before entering the gas-liquid separation device, and the gas content is less than 2% after flowing through the polytetrafluoroethylene hollow fiber membrane module.

[0158] Comparative Example 1

[0159] An absorption tower is used as a chemical absorption device (equipped with a simple degassing device). Take N2 / CO2 mixed gas (N2 accounts for 83%, CO2 accounts for 17%), absorbent (composed of 5% anhydrous piperazine, 38% N-methyl-diethanolamine, and 57% deionized water), and pass the mixed gas into the absorption tower. The CO2 in the mixed gas combines with the absorbent, and the degassing device is used to achieve preliminary gas-liquid separation. The CO2 content in the mixed gas is tested. The CO2 absorption rate in the mixed gas after absorption is 90.15%, and the absorption rate of the absorption liquid can reach 65%. The gas content of the CO2-rich absorption liquid is 55%, and the gas content is 25% after leaving the absorption tower.

[0160] Conclusion: The gas-liquid contact area in the ordinary absorption tower is insufficient, the CO2 absorption effect is poor, and the absorption rate is low. At the same time, the degassing efficiency of the existing degassing device is poor, and the gas content of the CO2-rich absorption liquid is still high, which brings difficulties to the subsequent desorption process.

[0161] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A carbon dioxide microbubble absorption device, characterized in that: The carbon dioxide microbubble absorption device comprises a microbubble dispersion device, an absorption device, and a gas-liquid separation device; The microbubble dispersion device is filled with a Janus hollow fiber membrane; The water contact angle of the hydrophilic layer of the Janus hollow fiber membrane is less than 70°, and the water contact angle of the hydrophobic layer is greater than 100°; The Janus hollow fiber membrane has an inner diameter of 0.7-0.8 mm, an outer diameter of 1.2-1.4 mm, and a pore size of 0.2-0.3 μm; The gas-liquid separation device is filled with a hydrophobic separation membrane; The hydrophobic separation membrane is selected from at least one of a polytetrafluoroethylene hollow fiber membrane, a polypropylene hollow fiber membrane, and a polyvinylidene fluoride hollow fiber membrane.

2. The carbon dioxide microbubble absorption device according to claim 1, characterized in that: The microbubble dispersion device is provided with an inlet I-1, an inlet I-2, and an outlet I; The inlet I-1 is the absorption liquid inlet; The inlet I-2 is a mixed gas inlet; The absorption device is provided with an inlet II and an outlet II; The gas-liquid separation device is provided with an inlet III, an outlet III-1, and an outlet III-2.

3. The carbon dioxide microbubble absorption device according to claim 2, characterized in that: The outlet I is connected to the inlet II pipeline; The outlet II is connected to the inlet III through a pipeline.

4. The carbon dioxide microbubble absorption device according to claim 1, characterized in that: The Janus hollow fiber membrane is obtained by the following steps: The inner layer membrane-making liquid and the outer layer membrane-making liquid are introduced into the spinning core liquid by using a double-channel nozzle, and co-extruded to obtain a double-layer hollow fiber membrane, and the modified monomer is grafted to obtain the Janus hollow fiber membrane; The inner layer film-making solution contains a film-forming polymer A, an inner layer additive, an organic solvent A and an amphiphilic polymer A; The outer layer film-making solution contains a film-forming polymer B, an outer layer additive, an organic solvent B and an amphiphilic polymer B; The amphiphilic polymer A and the amphiphilic polymer B are independently selected from amphiphilic polymer I and amphiphilic polymer II; The amphiphilic polymer I is obtained by polymerizing a hydrophilic monomer I and a hydrophobic monomer I; The amphiphilic polymer II is obtained by polymerizing a hydrophilic monomer II and a hydrophobic monomer II; The hydrophilic monomer I is selected from at least one of allyl alcohol and butenol; The hydrophilic monomer II is selected from at least one of polyethylene glycol acrylate and vinyl pyrrolidone; The hydrophobic monomer I and the hydrophobic monomer II are independently selected from at least one of styrene, methyl acrylate, acrylonitrile and hexafluorobutyl acrylate; The amphiphilic polymer A in the inner layer film-forming solution and the amphiphilic polymer B in the outer layer film-forming solution are different from each other; The modified monomer is selected from at least one of hexafluorohexyltriethoxysilane and tridecafluorooctyltriethoxysilane; The film-forming polymer A and the film-forming polymer B are independently selected from at least one of polysulfone, polyethersulfone, polyvinylidene fluoride, polymethyl methacrylate, polyvinyl chloride and polyacrylonitrile; The inner layer additive is selected from at least one of polyethylene glycol, anhydrous lithium chloride and polyvinyl pyrrolidone; The outer layer additive is selected from at least one of polyethylene glycol, anhydrous lithium chloride and polyvinyl pyrrolidone; The organic solvent A and the organic solvent B are independently selected from at least one of dimethylacetamide, dimethylformamide, N-methylpyrrolidone and tetrahydrofuran; The mass concentration of the film-forming polymer A in the inner layer film-forming solution is 10-25wt%, the mass concentration of the inner layer additive is 5-20wt%, and the mass concentration of the amphiphilic polymer A is 1-20wt%; The mass concentration of the film-forming polymer B in the outer layer film-forming solution is 10-25 wt %, the mass concentration of the outer layer additive is 5-20 wt %, and the mass concentration of the amphiphilic polymer B is 1-20 wt %.

5. The carbon dioxide microbubble absorption device according to claim 1, characterized in that: The packing density of the Janus hollow fiber membrane packed in the microbubble dispersion device is 5-65%.

6. The carbon dioxide microbubble absorption device according to claim 1, characterized in that: The packing density of the hydrophobic separation membrane packed in the gas-liquid separation device is 5 to 65%.

7. The carbon dioxide microbubble absorption device according to claim 1, characterized in that: The number of the microbubble dispersion device and the gas-liquid separation device is independently selected from a positive integer between 1 and 10; A plurality of microbubble dispersion devices are connected in series or in parallel; A plurality of gas-liquid separation devices are connected in series or in parallel.

8. A method for carbon dioxide absorption and gas-liquid separation, characterized in that: A carbon dioxide microbubble absorption device as described in any one of claims 1 to 7 is used.

9. The method according to claim 8, characterized in that In the carbon dioxide microbubble absorption device, the gas pressure is 0.02-10 MPa, the liquid pressure is 0.01-10 MPa, and the gas-pressure differential is 0.001-0.3 MPa.

10. The method according to claim 8, characterized in that In the gas-liquid separation device, the temperature is 10-60° C. and the pressure is 0.01-0.05 MPa.

Citation Information

Patent Citations

  • Device and method for extracting bromine by using membrane process

    CN101565170A

  • Process method for capturing carbon dioxide in flue gas through membrane absorption of amino solution

    CN102228772A

  • Novel Janus polymer hollow fiber membrane and preparation method and application thereof

    CN109621734A

  • Janus polytetrafluoroethylene hollow fiber membrane and preparation method thereof

    CN110394068A

  • Hollow fiber membrane

    EP2567750A1